Pollution of Surface and Ground Water by Sources Related to Agricultural Activities - Sasakova, Nada; Gregova, Gabriela; Takacova, Daniela; Mojzisova, Jana; Papajova, Ingrid; Venglovsky, Jan; Szaboova, Tatiana; Kovacova, Simona (Frontiers in Sustainable Food Systems, 2018)
The objective of this study was to monitor the quality of ground water supplied to animal farms and 2 villages and of surface water (rivers) in the same area (Košice basin, eastern Slovakia) with the aim to assess contamination of water by potential sources in this area. Samples for physico-chemical and microbiological examination were collected at 12 sampling points (6—surface water; 6—ground water) from May 2014 up to March 2015, covering all four seasons. The examination and evaluation of individual parameters was carried out according to relevant Slovak legislation compatible with EU Drinking water directive. The physico-chemical evaluation focused on parameters that indicate pollution of water resulting from human activities and farming. Microbiological examination included determination of counts of bacteria cultivated at 22°C and 37°C (BC22 and BC37), total coliforms, E. coli and fecal streptococci. Ground water intended for mass consumption (farms, villages) is abstracted from wells, collected in storage reservoirs and disinfected before brought to consumers. Some families in the villages use their own wells. Water for individual consumption (individual households) originates directly from individual wells. Examination of potable water used on agricultural farms showed some possibility of contamination of sources by runoff and inappropriate manipulation with excrements. Surface water in in the area close to both farms was polluted with organic substances (CODMn), however they did not exceed the limit set for surface water. At many samplings we detected in surface water presence of total coliforms, E. coli and occasionally also fecal enterococci indicating fecal pollution that could eventually affect ground water in individual wells. Our investigations showed that protection zones of water sources were not always sufficient. There were considerable variations in the quality of surface water during the year but no clear relationship between microbial contamination and seasons was observed. Quality of ground water supplied for mass consumption complied with legislative regulations except for BC 22 (heterotrophic count at 22°C) in summer and autumn). Water from individual wells contained occasionally presence of total coliforms, E. coli and enterococci and higher heterotrophic counts.